From Baghdad to Jambi: The Story of Syekh Maulana Qori and the Sacred Tomb in East Muaro Panco Village, Muaro Panco - Rasyadi, Imron; Malik, Abdul; Ibrahim, Ibrahim (Pusat Studi Aswaja An-Nahdliyyah UNISNU Jepara, 2024)
The objectives of this research are to identify and examine historical facts pertaining to the sacred grave site in East Muaro Panco Village, Renah Pembarap District, Merangin Jambi. The local community believes that the tomb belongs to the great and sacred scholar Syekh Maulana Qori, who is said to have travelled from Baghdad to spread Islam in Jambi. However, this narrative is largely based on oral tradition and lacks corroboration from historical sources. The researchers employed a qualitative research approach with a case history methodology in order to address the aforementioned concern. Data was gathered through interviews with informants, including community leaders, religious leaders, and Kyai, both within and outside the area, who were deemed to possess knowledge of the tomb’s history. Subsequently, researchers conducted direct observations at the tomb and utilized documentation pertaining to the history of Syekh Maulana Qori. The results of the researchers’ search yielded a history of the tomb in Muaro Panco, which revealed that it was the final resting place of Syekh Maulana Qori, a prominent scholar from Baghdad (Iraq) who was related to Syekh Al-fairus Al-Baghdadi. Syekh Maulana Qori is regarded as one of the most influential Islamic scholars in Muaro Panco’s history. His grave remains a pilgrimage site, both locally and from beyond the region, including from outside Indonesia.